Colonic Manifestations and Complications Are Relatively Under-Reported in Systemic Sclerosis: A Systematic Review. (December 2019) - Brandler, Justin B.; Sweetser, Seth; Khoshbin, Katayoun; Babameto, Mary; Prokop, Larry J.; Camilleri, Michael
Abstract : OBJECTIVES: Although systemic sclerosis (SSc) is known to affect the gastrointestinal (GI) tract, most of the literature focuses on esophageal, small intestinal, or anorectal manifestations. There have been no reviews focused on large bowel SSc complications in over 30 years. The aim of this study is to perform a systematic review of colonic manifestations and complications of SSc. METHODS: An experienced librarian conducted a search of databases, including English and Spanish articles. The search used keywords including "systemic sclerosis, " "scleroderma, " and "colon." A systematic review was performed using Preferred Reporting Items for Systematic Review and Meta-Analyses guidelines. Case reports/series were screened for validity by adapting from criteria published elsewhere. RESULTS: Of 1, 890 articles, 74 met selection criteria. Fifty-nine of the 77 articles were case reports/series. The most common article topics on colonic SSc complications were constipation/dysmotility (15), colonic volvulus (8), inflammatory bowel disease (7), microscopic colitis (6), megacolon (6), and telangiectasia (6). Colonic manifestations constituted 24% of articles on GI complications of SSc. There were a total of 85 cases (84% women, with a median age of onset of colon complication of 52 years). Limited cutaneous SSc phenotype (65.6%) was more common than diffuse (26.2%). Patients frequently had poor outcomes with high mortality related to colonic complications (27%). Recent studies explore contemporary topics such as the microbiome in SSc and prucalopride for chronic constipation in SSc. DISCUSSION: Colonic complications comprise a large proportion of the published reports on GI symptoms afflicting patients with SSc and require raised diagnostic suspicion and deliberate action to avoid potentially serious complications including death.